EVALUASI PERFORMANCE REGENERASI MIXED BED POLISHER PADA UNIT DEMINERALISASI - Irhamni Nuhardin; Mimin Septiani; Ronaldo Rivaldiansyah (Mechanical Engineering Departement - Universitas Tridharma, 2021)
One of the important elements produced from the factory support units is air products. Regional water balance (integration) is important to support factory operations. Raw water is treated in the unit section to produce demin water and further process into Boiler Feed Water (BWF) to produce 80 kg/cm2 pressurized steam in the boiler unit, to meet the specifications as demin water it is necessary to carry out several treatments to remove mineral ions (cations and anions) dissolved in the air. In the mixed bed polisher, there is a resin regeneration process to eliminate saturation of the resin which can no longer bind mineral ions. Regeneration or regent is carried out after the resin pile is saturated which is characterized by an increase in product productivity conductivity with the desired product conductivity target of <0.2 μS/cm at a temperature of 25℃. The purpose of this study was to work or perform a mixed bed polisher, especially during regeneration in the demineralization unit. This research was conducted by making a framework of thought and writing work. The writing stage contains data collection, data processing and data analysis-synthesis, as well as drawing conclusions. Based on this research, the results showed that there was a decrease in the performance of the mixed bed with a bed expansion gain of 80.7% and a resin height of 2.42 m. The number of chemicals used for regeneration is 1170.7 kg consisting of HCL and NaOH so that the flow rate of demin water required to dilute the regenerant is 7,126 m3/h. Keywords: Mixed bad Polisher, Demin water, Resin regeneration.